A Greek and Arabic lexicon (GALex) (Leiden ; Boston)
2 cilt (1. c. lviii, 668 sayfa ; 2. c. xlvi, 719 sayfa)
Keywords: “From the 8th to the 10th century AD, Greek scientific and philosophical works were translated wholesale into Arabic, sometimes through the mediation of Syriac. A Greek and Arabic Lexicon is the first attempt to present in a systematic and rationalized way, with full analysis of the categories describing the grammar of translation, the vocabulary of these translations as each term appears in context, fully cited. It is an indispensable reference tool for the study and understanding of Arabic scientific and philosophical language and literature and its grammar, the vocabulary of Classical and Middle Greek, the transmission of the text of classical Greek works and their reception in late antiquity and Byzantium, and the reception and translation of the Arabic literature based on them in Byzantine Greek. Fully indexed, this second edition of the work supersedes the first with enhanced precision and breadth of coverage and user-friendly philological analysis“ -- Yayıncı.